Answer:
Explanation:
n(-2) = -1 - (-2) + 4 = -1 + 2 + 4 = -1 + 6 = 5
( - 1 , 6 one has +sign and other -sign. So different sign mean, we have subtract and the sign of the result will be the bigger number's sign. Here bigger number [6] is +. So, result is 5)
n(0) = -1 - 0 + 4 = -1 + 4 = 3
n(5) = - 1 - 5 + 4 = -6 + 4 = -2
( -6 , 4 one has +sign and other -sign. So different sign mean, we have subtract and the sign of the result will be the bigger number's sign. Here bigger number [-6] is -. So, result is -2)